Perancangan Dan Implementasi Aplikasi Pengelolaan Data Magang Dan Riset Menggunakan Framework Laravel Pada RSUD Siti Fatimah Palembang - Rahmania, Desti; Sutabri, Tata; Sopiah, Nyimas; Rizal, Syahril (Jusikom : Jurnal Sistem Komputer Musirawas, 2024)
The management of internship and research activities in hospitals requires an efficient and structured system to monitor and document the registration process. In the context of RSUD Siti Fatimah Palembang, improving efficiency and accuracy in managing the registration of internship and research activities is essential to enhance services for internship participants. Therefore, this study aims to design and implement a web-based internship and research data management application using the Laravel framework. The data collection methods consist of interviews, observations, documentation, and literature review. The system development method using the Laravel framework involves needs analysis, planning, system design, implementation, testing, management and maintenance, user training, and evaluation. These stages will form a structured system development framework tailored to user needs. The result of this research is a website application for managing internship and research data that provides features to support online registration for internships and research.